2021
DOI: 10.3390/nano11082138
|View full text |Cite
|
Sign up to set email alerts
|

Pool Boiling Amelioration by Aqueous Dispersion of Silica Nanoparticles

Abstract: Non-metallic oxide nanofluids have recently attracted interest in pool boiling heat transfer (PBHT) studies. Research work on carbon and silica-based nanofluids is now being reported frequently by scholars. The majority of these research studies showed improvement in PBHT performance. The present study reports an investigation on the PBHT characteristics and performance of water-based silica nanofluids in the nucleate boiling region. Sonication-aided stable silica nanofluids with 0.0001, 0.001, 0.01, and 0.1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…An excessive nanoparticle deposition may cause the thickening of the deposition layer, which in turn, may lead to an increase in the thermal resistance and, consequently, to the pool-boiling heat-transfer deterioration. This fact was confirmed through the experimental work conducted by the researchers Mukherjee et al [ 88 ] using silica nanofluids having different volume fractions. The authors reported that with lower concentrations of 0.0001 vol.…”
Section: Main Factors Impacting the Nanoparticle Depositionmentioning
confidence: 53%
“…An excessive nanoparticle deposition may cause the thickening of the deposition layer, which in turn, may lead to an increase in the thermal resistance and, consequently, to the pool-boiling heat-transfer deterioration. This fact was confirmed through the experimental work conducted by the researchers Mukherjee et al [ 88 ] using silica nanofluids having different volume fractions. The authors reported that with lower concentrations of 0.0001 vol.…”
Section: Main Factors Impacting the Nanoparticle Depositionmentioning
confidence: 53%
“…Other experiments [ 10 , 63 , 69 , 70 , 71 ] observed a change in the typical boiling performance of water when using nanoparticle suspensions, attributed to the deposition of nanoparticles on the heated surface forming a porous layer. The deposited porous layer was found in some cases [ 69 , 70 ] to enhance the HTC until a certain concentration of nanoparticles, and then degrade it. At low concentrations, a small amount of deposition led to an increased bubble emission frequency by providing additional nucleation sites [ 69 , 72 ].…”
Section: Results On the Effect Of Nanoparticles On Pool Boilingmentioning
confidence: 99%
“…Moreover, the obtained thermophysical properties were later used in the mathematical modelling of the intercooler. In terms of the physical stability of the as-prepared dispersions, it was visually determined using the photographic image capturing method [ 18 , 30 ] directly after the preparation of the nanofluids and up to 45 days.…”
Section: Methodsmentioning
confidence: 99%